From genes to organs: physiological responses of European chub (Squalius cephalus) to chronic PFAS pollution - Pacchini, Sara; Drago, Laura; Cortese, Martina; Vanzan, Giacomo; Piva, Elisabetta; Kholdihaghighi, Shaghayegh; Barbarossa, Andrea; Bardhi, Anisa; Schumann, Sophia; Fogliano, Chiara; Bottacin-Busolin, Andrea; Irato, Paola; et al. (Frontiers in Toxicology, 2025)
Per- and polyfluoroalkyl substances (PFAS) are widespread anthropogenic contaminants known to the scientific community for their persistence and toxicity. Our research aims to evaluate the effect of chronic environmental exposure to PFAS on the antioxidant system of Squalius cephalus. In particular, to better understand how various components of the antioxidant system act together to counteract the adverse effects of PFAS, in the present study we evaluate the gene expression and enzymatic activity of two selenium-dependent glutathione peroxidases (namely GPx-1 and GPx-4) and the catalase, in the two major organs involved in the accumulation and detoxification from pollutants, including PFAS, i.e. liver and caudal kidney. Fish were sampled from four sites in the Veneto region with different concentrations of total dissolved PFAS. To better assess the acclimatisation to the environment, the morphological characteristics of the fish were also examined, as well as the development of organs, through the calculation of some somatic indices. Lipid accumulation was demonstrated histologically in both the liver and caudal kidney, which likely occurs to attenuate the high reactivity of PFAS toward protein content in these organs. The results demonstrate how Squalius cephalus can survive chronic PFAS exposure through cellular and systemic physiological responses.